Agambens kairologi:: Erfaring og den messianske tid - Knudsen, Nicolai Krejberg (Slagmark - Tidsskrift for idéhistorie, 2015)
This article argues that Giorgio Agamben’s conceptions of kairos (the decisive moment) and messianic time are essentially to be understood in terms of experience. This becomes clear when we identify the methodological similarities between Agamben’s reading of Paulus in The Time That Remains and Heidegger’s lectures on Paulus from 1920-21: the doctrine of kairology is different from any eschatology, insofar as it involves an instantaneous modulation of our factical conditions, rather than a removal of them (always yet) to come. In this way, I argue that Agamben echoes Heidegger’s conception of formal indication and enactment-sense. But whereas Heidegger understood this modulation as an anticipatory resoluteness, in which Dasein identifies itself with its calling, Agamben emphasizes the very impossibility of such an identification. This is indeed a decisive difference between Agamben and Heidegger. I show, however, that Agamben phrases this difference in a language that recalls Heidegger’s thought, thus implicitly suggesting that the emancipatory potential of his philosophy is to be understood as the experiential enactment of an impotentiality that undermines any factical condition and any social identity.